Sysematic Literature Review on Purchase Decisions of Islamic Insurance in Indonesia - Hanif, Syarifa; Hardiansyah, Hardiansyah; Rusydiana, Aam (Universitas Islam Negeri Raden Intan Lampung, 2024)
The growth of the Islamic insurance industry is still not growing significantly when compared to the Muslim population in Indonesia. Therefore, this study aims to determine the factors that influence the purchase decision of Islamic insurance. This research is a qualitative research with a systematic literature review method supported by the PRISMA approach. Results of this study shown that psychological factors, individual factors, marketing factors and cultural factors are successively the factors that most influence the purchase decision of Islamic insurance.